Targeting DOT1L and EZH2 synergizes in breaking the germinal center identity of diffuse large B-cell lymphoma - Göbel, Camiel; Niccolai, Rachele; de Groot, Marnix H P; Jayachandran, Jayashree; Traets, Joleen; Kloosterman, Daan J; Gregoricchio, Sebastian; Morris, Ben; Kreft, Maaike; Song, Ji-Ying; Azarang, Leyla; Kasa, Eirini; et al. (Blood, 2025)
Differentiation of antigen-activated B cells into proproliferative germinal center (GC) B cells depends on the activity of the transcription factors myelocytoma (MYC) and B-cell lymphoma 6 (BCL6), and the epigenetic writers disruptor of telomeric silencing 1-like (DOT1L) and enhancer of zeste homolog 2 (EZH2). GCB-like diffuse large B-cell lymphomas (GCB-DLBCLs) arise from GCB cells and closely resemble their cell of origin. Given the dependency of GCB cells on DOT1L and EZH2, we investigated the role of these epigenetic regulators in GCB-DLBCLs and observed that GCB-DLBCLs synergistically depend on the combined activity of DOT1L and EZH2. Mechanistically, inhibiting both enzymes led to enhanced derepression of polycomb repressive complex 2 target genes compared with EZH2 single treatment, along with the upregulation of BCL6 target genes and suppression of MYC target genes. The sum of all these alterations results in a "cell identity crisis," wherein GCB-DLBCLs lose their proproliferative GC identity and partially undergo plasma cell differentiation, a state associated with poor survival. In support of this model, combined epidrugging of DOT1L and EZH2 prohibited the outgrowth of human GCB-DLBCL xenografts in vivo. We conclude that the malignant behavior of GCB-DLBCLs strongly depends on DOT1L and EZH2 and that combined targeting of both epigenetic writers may provide an alternative differentiation-based treatment modality for GCB-DLBCL.